A Multi-Level Study on the Anti-Lung Cancer Mechanism of Peiminine, a Key Component of Fritillaria ussuriensis Maxim.: Integrating Quality Analysis, Network Pharmacology, Bioinformatics Analysis, and Experimental Validation - Yang, Ziwen; Syed Faizan Ali, Shah; Huang, Xinhui; Wei, Lin; Zhong, Yinze; Shi, Xuepeng; Wu, Xiaotian; Gan, Chunli; Wang, Zhibin; Yang, Chunjuan (International journal of molecular sciences, 2025)
Globally, lung cancer is the primary cause of deaths associated with cancer; however, current therapies are costly and toxic, highlighting the need for novel treatments. Peiminine (Verticinone), a key bioactive compound derived from Fritillaria ussuriensis Maxim., has demonstrated diverse biological activities. However, the precise pharmacological mechanisms underlying its anti-lung cancer effects remain unclear. The objective of this study was to quantify the content of peiminine in Fritillaria ussuriensis Maxim. from different geographical regions using UHPLC-MS/MS and to elucidate the anti-lung cancer mechanisms of peiminine through network pharmacology, bioinformatics, and in vitro experiments. The content of peiminine in Fritillaria ussuriensis Maxim. from various regions was determined using UHPLC-MS/MS. Potential target genes associated with peiminine and lung cancer were systematically screened from multiple databases. To identify core genes, we set up a PPI (protein–protein interaction) network, followed by in-depth analyses of their corresponding target proteins. Survival analysis, molecular docking, and dynamics simulations were used to explore potential anti-cancer mechanisms. In vitro experiments on human H1299 NSCLC cells assessed peiminine’s anti-tumor activity and measured key gene transcription levels. UHPLC-MS/MS analysis revealed that Fritillaria ussuriensis Maxim. from Mudanjiang (Heilongjiang Province) exhibited the highest peiminine content. Network pharmacological analysis identified PIK3CG, SRC, JAK3, AKT2, and PRKCA as key potential targets of peiminine in lung cancer treatment. Molecular docking results demonstrated strong binding affinities between peiminine and PIK3CG, SRC, and JAK3; these results were further confirmed using molecular dynamics simulations. Survival analysis indicated that a high AKT2 and PRKCA expression correlated with bad prognosis in lung cancer patients. In vitro, peiminine inhibited H1299 cell viability and regulated genes involved in the PI3K–Akt pathway (PI3K, AKT, and PTEN) and apoptosis (Bcl-2, Bax), suggesting that it may induce its effects via PI3K–Akt pathway inhibition. Peiminine from Fritillaria ussuriensis Maxim. exhibits significant anti-lung cancer potential by targeting key genes such as PIK3CG, SRC, and JAK3, as well as by modulating the PI3K-Akt signaling pathway and apoptosis-related genes. These results lay a foundation for further investigations into peiminine as a potentially effective therapeutic option for treating lung cancer. Additionally, the identified targets (PIK3CG, SRC, JAK3, AKT2, and PRKCA) may function as possible biomarkers for predicting lung cancer prognosis and guiding personalized therapy.